MOTIVATION OF PROSPECTIVE ECONOMIC TEACHER CANDIDATES AND THEIR RELATIONSHIP WITH RELIGIOSITY - Arrahmah, Nabilah; Mintasih Indriayu; Muhammad Sabandi (Jurnal Tinta, 2024)
This research focuses on the influence of religiosity on motivation to become economics teachers among students who are studying for teachers at universities. A total of 100 students filled out the survey questionnaire that was distributed. The level of religiosity is measured using the intrinsic religiosity scale and motivation to become a teacher is based on Ryan & Deci's motivation theory, namely self-determination theory. The results of this study found that religiosity has a significant effect on motivation to become an economics teacher. However, there is no significant difference between male and female students in becoming teachers.